The Principle of Crimes and Penalties Overlapping in Saudi Criminal Law - Aljadhay, Mohammed. F. (Journal of Ecohumanism, 2025)
The study aims to identify the crime principle and Ta’zir (discretionary) penalties in terms of nature, domain, and status- It also highlights the position of the Arab legislative stance regarding the issue of overlapping and the Saudi situation toward it. In addition, it attempts to unveil patterns of crimes, discretionary penalties, and the correlation between crimes overlapping and apparent text conflict of criminal penalties. The study adopted the descriptive analytical approach, which analyzes legal texts on the issue, besides jurists’ attitudes relevant to the subject, to check what is in force among them. It also used the comparative approach to compare how other countries deal with the principle of overlapping with discretionary penalties and the extent to which the Saudi legislative law might benefit from the experience of those countries in developing its penal law. The study concluded that, according to the mechanism put down by the Saudi penal law, the principle of overlapping is taken into account only when the case is officially considered a crime. When it proves so, the penalty should be the most severe, as stated against penalties of the original type. The principle can be realized whenever several indivisibly correlated crimes are committed for the same purpose. In such a case, all crimes are considered one and shall receive the most severe kind of penalty inflicted upon any of them, pending that the sentence does not violate the original penalty against the corollary and complementary provisions for such crimes. In light of the findings, the study proposes numerous recommendations, the foremost of which is: to conduct further legal, social, and psychological studies to track the reasons behind committing overlapping crimes by any individual to understand the criminal’s behavior to bridge the gaps found in such crimes.